The Dance Of Sacred Water - Gde Agung Rahma Putra, Anak Agung; Sedana, I Nyoman (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
The Dance of Sacred Water featuring water in culture and religion is a brand new dance uniquely choreographed and presented for the academic commitees and the public audiences as part of an academic requirement to complete my Ph.D degre in Dance Department, Indonesian Arts Institute Surakarta, Middle-Java. The original title of this Ph.D final performance dissertation in local language is “Tari We Beji Langon” (literary means the Dance of Aqua Culture and Religion), presented in a newly chorepgraphed dance composition integrating dance, narration, song, and gamelan music. It is designed as a site specific choreography, inspired by the significant values of water surrounding the Beji Langon water spring. Located in Kapal Village, Mengwi District, Badung Regency, this water spring is still preserved by the local community as holy hydrospherec resorces. Choreographed and performed surrounding this natural environment instead of in a conventional theatre, the dance portrays elevating aqua culture in upgrading level of human purposes. The dacers start from the river where water employed in profane daily life, then they move to the outpouring water for various Hindu ritual ceremonies, until finally recounting holy water as tirtha from spring water for spiritual purification. This dance depicts ascending realms of profane-ordinary-sacred water according to the use of water in various aspects of Balinese Hindu community as often mentioned in Balinese lontar manuscripts. This choreography is the result of exploration on aqua culture among Balinese people who have recently begun to experience abrasion. Based on practice-based research this dance aims to convey the values of local Balinese wisdom regarding the essential role of water in the sociocultural and religious life of the Hindu Bali community. The performance of this dance is expected to reinforce the awareness and enlightenment of the local people around the location of the Beji Langon bathing area to always maintain the cleanliness and purity of the water and to preserve its surrounding environment.